Detection of anti-viral antibodies from meat juice of wild boars - YONEMITSU, Kenzo; MINAMI, Shohei; NOGUCHI, Keita; KUWATA, Ryusei; SHIMODA, Hiroshi; MAEDA, Ken (Journal of Veterinary Medical Science, 2019)
Wild boars are a reservoir for many zoonotic pathogens and a good sentinel for surveillance of zoonotic viral infections, but collection of serum samples from wild boars in the field is sometimes difficult and requires special equipment and techniques. In this study, ELISA using meat juices extracted from the heart and diaphragm of wild boars, instead of serum samples, was performed to detect antibodies against zoonotic pathogens, Japanese encephalitis virus and hepatitis E virus. The results of ELISA using meat juice samples were significantly correlated with those using serum samples and meat juice contained one-fifth the antibodies of serum samples. As meat juice is easily collected from wild animals in the field without special equipment and techniques, ELISA using meat juice is a simple and superior method for serological survey of zoonosis among wild animals.